The Effect of Injector Performance on Exhaust Gas Temperature Diesel Generator Engine on Ship - Muhamad Fikri Supriatmana; Nasri; Wulan Marlia Sandi; Monika Retno Gunarti; Intan Sianturi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Injectors play a crucial role in optimal combustion of marine diesel generator engines, but their performance degradation often causes exhaust gas temperature fluctuations that reduce efficiency and operational reliability. This study aims to analyze the effect of injector performance on exhaust gas temperature on the SV. STELLA 28 vessel. Using a causal descriptive quantitative approach, the population is operational data of Auxiliary Engine 1 and 2 for 12 months, with a purposive sample of 70 observations. Instruments include injector maximum pressure (PMAX) measurements and exhaust gas temperature thermocouples, analyzed through the Kolmogorov-Smirnov normality test, simple linear regression, and SPSS. The results show a significant effect (Sig. 0.000) with R² 0.417 and the equation . The conclusion states that optimal injector performance stabilizes exhaust gas temperature, supporting condition-based maintenance.